2002
DOI: 10.1182/blood.v99.1.258
|View full text |Cite
|
Sign up to set email alerts
|

Tissue inhibitor of metalloproteinases 1 is an autocrine and paracrine survival factor, with additional immune-regulatory functions, expressed by Hodgkin/Reed-Sternberg cells

Abstract: Tissue inhibitor of metalloproteinases (TIMP)-1 and TIMP-2 are proteins with proteinase-inhibiting and cytokine properties. TIMP-1 is active primarily in B cells and B-cell lymphomas, whereas TIMP-2 expression is restricted to T cells. The expression of TIMP-1 and TIMP-2 in lymph nodes from patients with Hodgkin disease (HD) and in Hodgkin-derived cell lines was investigated. In situ hybridization showed TIMP-1 RNA expression in 3% to 80% of Hodgkin/Reed-Sternberg (H/R-S) cells from 14 of 15 patients, with res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
2
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 82 publications
0
41
2
2
Order By: Relevance
“…Real-time PCR data showed that the MMP-9/TIMP-1 ratio was noticeably higher in BEL-7402 than in the normal liver cell line L-02 and QSG-7701, TIMP-1 is a multifunctional protein with MMP-dependent and -independent actions for the regulation of cell death, cell proliferation, and angiogenesis (25). After TIMP-1 was initially characterized as a homologue of erythroid potentiating activity factor, it was found to display growth-and survivalpromoting activity for a wide range of normal or transformed cells (26,27). Increasing evidence demonstrates a much more complex role for TIMP-1 during tumor progression and angiogenesis, in addition to its regulation of MMP-mediated ECM degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Real-time PCR data showed that the MMP-9/TIMP-1 ratio was noticeably higher in BEL-7402 than in the normal liver cell line L-02 and QSG-7701, TIMP-1 is a multifunctional protein with MMP-dependent and -independent actions for the regulation of cell death, cell proliferation, and angiogenesis (25). After TIMP-1 was initially characterized as a homologue of erythroid potentiating activity factor, it was found to display growth-and survivalpromoting activity for a wide range of normal or transformed cells (26,27). Increasing evidence demonstrates a much more complex role for TIMP-1 during tumor progression and angiogenesis, in addition to its regulation of MMP-mediated ECM degradation.…”
Section: Discussionmentioning
confidence: 99%
“…23,30 Moreover, it has been shown that upregulation of TIMP-1 expression, in a BL cell line, is related to the activation of STAT3. 3 It has been shown that TIMP-1 is expressed in Reed-Sternberg cells of Hodgkin lymphoma 31,32 and subsets of high grade B-cell lymphoma. 4,5 More recently, the existence of a gray zone between diffuse large B-cell lymphoma and Hodgkin lymphoma has been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this possibility, CD63 has been shown to deliver co-stimulatory signals to T cells 25 and exert an anti-apoptotic effect on other cell types. 26 The interaction between TIMP-1 and haematologica | 2010; 95(11) CD63 may also be involved in the capacity of TIMP-1 to inhibit cell-mediated cytotoxicity, reported by other authors, 27 since CD63 marks the cytolytic granules of cytotoxic cells and its surface expression is increased in active cytotoxic cells. This inhibitory effect may play a role in the development of ALPS and DALD since cellmediated cytotoxicity may partly compensate the apoptosis defect in these diseases.…”
Section: Discussionmentioning
confidence: 99%